PERAN PETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PROGRAM KAMPUNG KB - Amalia, Nisa Ayu; Mumu, Mumu; Adi Laksono, Bayu (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
In this research there is a lack of community participation in the KB village program. Family Planning Field Officers (PLKB) as one of the spearheads in the family planning program. The purpose of this research is to see how the role of Family Planning Field Officers (PLKB) as an agent of change in increasing community participation in the KB village program. The research method used in this research is a qualitative research approach with descriptive research. The results of the study show that the role of the Family Planning Field Officer (PLKB) in increasing community participation is by doing various ways such as providing opportunities for the community to negotiate, mediation and deliberation, providing support and encouragement to the community, fostering community awareness, providing information and knowledge to the community, connecting the community, The conclusion of this research is that with the role of Family Planning Field Officers (PLKB), the community said that they were greatly helped and increased their curiosity and sense of participation with the lessons and information from the results of counseling conducted by the Family Planning Field Officers (PLKB). Key words: Role, PLKB, Community Participation